Regulation of glucose homeostasis by small RNA mediated activation of sugar phosphatase mRNA - Papenfort, Kai (2013)
Glucose homeostasis is strictly controlled in all domains of life. Bacteria that are unable to balance intracellular sugar levels and deal with potentially toxic phosphosugars cease growth and risk being outcompeted. Here, we identify the conserved haloacid dehalogenase (HAD)-like enzyme YigL as the previously hypothesized phosphatase for detoxification of phosphosugars, and reveal that its synthesis is activated by an Hfq dependent small RNA in Salmonella typhimurium. We show that the glucose-6-P-responsive small RNA SgrS activates synthesis YigL in a translation-independent fashion, by the selective stabilization of a decay intermediate of the dicistronic pldB-yigL mRNA. Intriguingly, the major endoribonuclease RNase E, previously known to function together with small RNAs to degrade mRNA targets, is also essential for this process of mRNA activation. The exploitation of and targeted interference with regular RNA turnover described here may constitute a general route for small RNAs to rapidly activate both coding and noncoding genes.